Spent coffee grounds-based activated carbon preparation for sequestering of malachite green - Lim, J.-W. (American Institute of Physics Inc., 2016)
The key of reported work was to optimize the fabricating factors of spent coffee grounds-based activated carbon (SCG-bAC) used to sequester Malachite Green (MG) form aqueous solution via adsorption process. The fabricating factors of impregnation ratio with ortho-phosphoric acid, activation temperature and activation time were simultaneously optimized by central composite design (CCD) of response surface methodology (RSM) targeting on maximum removal of MG. At the optimum condition, 96.3 of MG was successfully removed by SCG-bAC at the impregnation ratio with ortho-phosphoric acid of 0.50, activation temperature of 554Â°C and activation time of 31.4 min. Statistical model that could predict the MG removal percentage was also derived and had been statistically confirmed to be significant. Subsequently, the MG adsorption equilibrium data was found well-fitted to Langmuir isotherm model, indicating the predominance of monolayer adsorption of MG on SCG-bAC surface. To conclude, the findings from the this study unveil the potential of spent coffee grounds as an alternative precursor in fabricating low-cost AC for the treatment of wastewater loaded with MG pollutant. Â© 2016 Author(s).